Secondary school Student's perspectives about nursing career and their motivations to become future nurses in Singida municipal: A qualitative study - Rehema Bakari Omari; Pendo Paschal Masanja; Golden Mwakibo Masika; Mahamudu Rashid Hussein (Wiley, 2023)
Abstract Aim To explore secondary school students' perspectives about nursing careers and their motivations to become future nurses. Design Qualitative descriptive design. Methods A qualitative study was conducted among secondary school students in Central Tanzania. Secondary school students who study science subjects and are eligible for nursing studies were selected from two schools. Two focus‐group discussions, comprising seven and eight students per group, one in each school, were conducted. The data were transcribed verbatim and analysed using qualitative thematic analysis. Results Two themes with seven sub‐themes emerged representing students' perspectives about nursing and the factors that motivate them to choose nursing as their future career. These themes are as follows: (1) Perspectives about a nurse and nursing, with five sub‐themes: (i) nurses' roles; (ii) qualities of nurses; (iii) workplace for nurses; (iv) nature of the job; and (v) position of a nurse or nursing; and (2) Motivations to become future nurses, with two sub‐themes: (i) extrinsic factors, and (ii) intrinsic factors.